Water in the urban space of Dubrovnik - Ipšić, Irena (Array, 2019)
Many city wells and public cisterns, along with the water supply system built from the spring in Šumet to the urban centre in the fifteenth century, are an eloquent testimony of the great concern of the Dubrovnik authorities to provide its inhabitants with a sufficient and regular supply of fresh water. The mapping of public water locations inside the walled city area indicates the elite urban parts inhabited by the bulk of the nobility. Prior to the construction of the aqueduct, it was the area of Bunićeva poljana, today's Ulica od puča, in which the majority of wells had been dug. After the construction of the aqueduct, and in conformity with new communal solutions, the elite part shifted northwards, around the Placa, main street, which transformed into a new city centre.